Management and Accounting Treatment of Zakat Based on PSAK 109 at BAZNAS Makassar City - Sri Rahayu Syah; Sufardi Sufardi; Rahmi Pahrisa; Ria Rezki Amalia; Alfiyatul Qomariyah; Sultan Syah (Universitas Dharmawangsa, 2026)
This study aims to analyze the management and accounting treatment of zakat based on PSAK No. 109 at the National Zakat Agency (BAZNAS) Makassar City. This study is motivated by the importance of transparent and accountable zakat management in accordance with sharia provisions and accounting standards. Zakat management in Indonesia is regulated by Law No. 23 of 2011 and reinforced by Government Regulation No. 14 of 2014. The research focuses on the collection, distribution, and utilization of zakat funds based on Law No. 23 of 2011, while the recording and reporting of zakat funds are analyzed based on PSAK No. 109 on Accounting for Zakat, Infaq, and Sadaqah. This study employs a qualitative method with a descriptive approach. Data were obtained through interviews, observations, and documentation of informants directly involved in zakat management at BAZNAS Makassar City. Research findings indicate that zakat funds are collected through professional zakat deductions, Zakat Collection Units, bank transfers, and zakat pickup services. Zakat distribution is carried out through programs in education, health, productive economy, social welfare, and religious outreach. Zakat accounting treatment generally refers to PSAK No. 109, which covers the recognition, measurement, presentation, and disclosure of zakat funds. However, there are still obstacles in the form of limited human resources, manual recording systems, and suboptimal digitalization of financial reporting